Alice Munro : hateship,friendship,courtship,marriage,runaway,dear life - Thacker, Robert (Bloomsbury studies in contemporary North American fiction, 2016)
"The Nobel Prize in Literature awarded to the Canadian writer Alice Munro in 2013 confirmed her position as a master of the short story form. This book explores Munro's work from a full range of critical perspectives, focusing on three of her most popular and important recent collections: Hateship, friendship, courtship, loveship, marriage (2001), Runaway (2004), and what is probably her final collection Dear life (2012). With chapters written by the world's leading critics of Munro's work, the short story form and contemporary Canadian writing, this book explores such themes as love and marriage, sex, fate, gender, and humor in her writings as well as her approaches to narrative form and autobiography"--